The Influence of Social Media Marketing Communication on the Development of Malaysian Culture - Samuel Adolfo Mariano Sanam (Publikasi Indonesia, 2025)
The proliferation of social media has transformed marketing communication, offering new avenues for cultural promotion and tourism development. In Malaysia, platforms like Instagram, TikTok, and Douyin present significant potential for showcasing cultural heritage to both local and international audiences, yet their strategic effectiveness in promoting sustainable cultural tourism requires further exploration. This study examines the influence of social media marketing communication on the development and promotion of Malaysian culture through digital platforms such as Instagram, TikTok, and Douyin. Using the Importance-Performance Analysis (IPA) and Media Mix Plan Theory, the research evaluates the effectiveness of these platforms in increasing engagement, cultural awareness, and tourism interest among both local and international audiences. The findings indicate that video-based content, especially on TikTok, achieved the highest engagement rates due to fast-paced visuals, trending music, and effective use of hashtags and timing. Moreover, the campaign successfully contributed to the Sustainable Development Goals (SDG 4 and SDG 16) by fostering intercultural understanding and peace through creative cultural representation. The results highlight that social media is a strategic communication tool for promoting Malaysia’s cultural image and enhancing sustainable tourism initiatives. This study underscores the strategic role of social media as a powerful tool for sustainable cultural marketing. Academically, it enriches the literature on digital cultural tourism and SDG integration in marketing strategies. Practically, it provides actionable insights for cultural organizations and tourism boards to design authentic and effective digital campaigns that boost cultural preservation, economic vitality, and global cultural image.